ХАЛЫҚ ШАЙЫРЛАРЫНЫҢ ТӘРИЙПЛИК ШЫҒАРМАЛАРЫНДА АШЫҚЛЫҚ ТЕМАСЫНЫҢ ЖЫРЛАНЫЎЫ - Давлетов, Б.А. (SCIENCE and SOCIETY, 2024)
The article interprets the odes of folk poets. In particular, the theme of love, glorified in the odes of the poets Umar and Kazi Maulik, is explored through examples. The songs reveal the girl’s external and internal beauty, good manners, manners, intelligence, politeness, moral qualities, and symbolically comprehend the feelings of the lyrical hero who is in love with her.